PENERAPAN METODE ASUHAN KEPERAWATAN PROFESIONAL: ANALISIS MOTIVASI TERHADAP OPTIMALISASI KINERJA PERAWAT - Janes Jainurakhma (Jurnal Ilmiah Kesehatan Media Husada, 2022)
Nurse motivation is one of the factors that affect the performance of nurses. Good performance of a nurse is able to make one of the descriptions of the level of success of a hospital service, including in an effort to implement a method of professional nursing care in hospitals. The purpose of this study was to analyze the relationship between nurse performance motivation and the application of professional nursing care (MAKP) methods at Ferina Mother and Child Hospital, Surabaya. This research is non-experimental with the number of respondents 14 inpatient nurses (total sampling), the instrument used is a questionnaire that has been tested for validity and reliability, with data analysis using linear regression statistical tests. The results of the linear regression test obtained significant results, namely the motivation factor with a significance value of 0.032, there was a relationship between the motivation of nursing performance on the application of professional nursing care methods. The correlation value is positive 47,551 and each increase is 12%. The results of the study show that motivation is very much needed in the performance of nurses and the implementation of professional nursing care methods, breakthroughs and special attention from management are needed to increase the motivation of nurses so that the team model of professional nursing care can be carried out optimally so that patient satisfaction with services is achieved.